Imide‐Functionalized Heteroarene‐Based n‐Type Terpolymers Incorporating Intramolecular Noncovalent Sulfur∙∙∙Oxygen Interactions for Additive‐Free All‐Polymer Solar Cells. (16th August 2019) - Sun, Huiliang; Liu, Bin; Koh, Chang Woo; Zhang, Yujie; Chen, Jianhua; Wang, Yang; Chen, Peng; Tu, Bao; Su, Maoyao; Wang, Hang; Tang, Yumin; Shi, Yongqiang; et al.
Abstract: The aggregation/crystallinity of classic n‐type terpolymers based on naphthalene diimide and perylene diimide is challenging to tune due to their rigid and extended cores, leading to suboptimal film morphology. A new strategy for developing high‐performance n‐type terpolymers by incorporating imide‐functionalized heteroarenes is reported here to balance crystallinity and miscibility without sacrificing charge carrier mobilities. The introduction of thienopyrroledione (TPD) into the copolymer f‐BTI2‐FT results in a series of terpolymers BTI2‐xTPD having distinct TPD content. The irregular backbone reduces crystallinity, yielding improved miscibility with the polymer donor. More importantly, TPD triggers noncovalent S⋯O interactions, increasing backbone planarity and in‐chain charge transport. Such interactions also promote face‐on polymer packing. As a result, all‐polymer solar cells (all‐PSCs) based on BTI2‐30TPD achieve an optimal power conversion efficiency (PCE) of 8.28% with a small energy loss (0.53 eV). This efficiency is substantially higher than that of TPD (4.4%) or a BTI2‐based copolymer (6.8%) and is also the highest for additive‐free all‐PSCs based on a terpolymer acceptor. Moreover, the BTI2‐30TPD cell exhibits excellent stability with the PCE retaining 90% of its initial value after 400 h of aging. The results demonstrate that random polymerization using imide‐functionalized heteroarenes is a powerful approach to develop terpolymer acceptors toward efficient and stable all‐polymer solar cell PSCs. Abstract : A facile and highly effective approach to balance the crystallinity and miscibility of terpolymer acceptors is reported. Random incorporation of thienopyrroledione triggers noncovalent sulfur∙∙∙oxygen interactions, enabling optimized blend morphology and polymer orientation without sacrificing charge carrier mobility; hence, an excellent efficiency of 8.28% is obtained from additive‐free all‐polymer solar cell devices.